2002
DOI: 10.1124/jpet.301.2.720
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Modulation of Muscarinic Receptor Signaling: Alcuronium-Induced Conversion of Pilocarpine from an Agonist into an Antagonist

Abstract: Previous studies on allosteric interactions at muscarinic receptors have often focused on ligand-receptor binding interactions, because ligand binding seemed to reflect functional consequences. The prototypal allosteric agent alcuronium is known to bind with similar affinity to the M 2 subtype of muscarinic acetylcholine receptors whether or not the receptors are occupied by the agonist pilocarpine. To determine allosteric modulation of receptor signaling by alcuronium, the effects of pilocarpine were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Our current findings now also suggest that these modulator-induced conformations can also be "inverse agonist-like" with respect to their effects on regulation of receptor number. Indeed, Zahn et al (2002) have previously demonstrated inverse agonism for alcuronium in an assay of M 2 mAChR-mediated guanosine 5Ј-O-(3-thio)triphosphate turnover. Overall, our observations provide further support to the concept that efficacy at GPCRs encompasses a broader spectrum of receptor behaviors than the classic activation-deactivation paradigm (Kenakin, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Our current findings now also suggest that these modulator-induced conformations can also be "inverse agonist-like" with respect to their effects on regulation of receptor number. Indeed, Zahn et al (2002) have previously demonstrated inverse agonism for alcuronium in an assay of M 2 mAChR-mediated guanosine 5Ј-O-(3-thio)triphosphate turnover. Overall, our observations provide further support to the concept that efficacy at GPCRs encompasses a broader spectrum of receptor behaviors than the classic activation-deactivation paradigm (Kenakin, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, alcuronium has been shown to modulate the intrinsic efficacy of pilocarpine (Zahn et al, 2002), and the allosteric effects of strychnine on acetylcholine-stimulated guanosine 5Ј-O-(3-[…”
Section: Discussionmentioning
confidence: 99%
“…So far, only parallel shifts have been reported for the effect of gallamine on the concentration-response curves of agonists, including the partial agonist BM5, suggesting that gallamine modifies the affinity of agonists without influencing their intrinsic efficacy. In contrast, strychnine and alcuronium (Zahn et al, 2002) have been shown to reduce both the potency and maximal responses of muscarinic agonists through an allosteric mechanism. It has been shown that the allosteric shift in the concentrationresponse curve of a full agonist for eliciting a downstream response is equivalent to the product of the change in affinity (p, eq.…”
mentioning
confidence: 99%
“…This phenomenon has been intensively studied on muscarinic acetylcholine receptors (Tuček and Proška, 1995;Birdsall et al, 1996;Ellis, 1997;Holzgrabe and Mohr, 1998). Many features of allosteric modulation have been demonstrated: enhancement of agonist binding (Birdsall et al, 1997;Jakubík et al, 1997;Lazareno et al, 1998; and action , absolute subtype selectivity of allosteric action (Birdsall et al, 1997;Lazareno et al, 1998Lazareno et al, , 1999, mapping of ligand receptor interactions Trä nkle et al, 1998a), defined maximum effects on function (Lü llmann et al, 1969;Clark and Mitchelson, 1976), and modulation of receptor signaling efficacy (Zahn et al, 2002). All five muscarinic receptor subtypes are sensitive to allosteric modulation (Ellis et al, 1991) with many of the typical quaternary ammonium modulators such as gallamine, alcuronium, W84, and dimethyl-W84, exhibiting an M 2 subtype selectivity.…”
Section: H]nms Binding Tacrine and Duo3 Decrease [mentioning
confidence: 99%